Inventory Management Application of Medicine and Medical Equipment in Health Department Tulungagung - Diagustin Rahayu; Antok Supriyanto; Henry Bambang Setyawan (Jurnal Sistem Informasi Universitas Dinamika, 2018)
Health Department Tulungagung government is implementing elements in the field of health and Has the task to carry out part of regional affairs in the health field. Tulungagung Health Department should be able to manage the supply of drugs and medical equipment stored in the Warehouse Pharmacy and then distributed to 32 health centers throughout Tulungagung. In the field of medicine and health expiration time came very important role, so this is one factor that must be considered in the process of managing medications and medical equipment. Pharmacy clerk currently still experiencing difficulties in managing their inventory, because there is no application that can determine the need for medication and medical equipment as well as directly monitor the process FEFO and FIFO drugs and medical equipment in the Health Service Pharmacy Warehouse Tulungagung.To solve the above problems, then built an application that can assist in the management of drug supplies and medical equipment to the Health Department Tulungagung. This application can perform data management, storage location search, calculation of needs, monitoring of drug FEFO and FIFO medical equipment, inventory monitoring and data management expired drugs.Conclusion of the application can perform management of medicines and medical equipment with more attention to the expiration dates of medicines and medical equipment came time using the First Expired First Out (FEFO) and First In First Out (FIFO).